Keterlibatan Spiritual Remaja melalui Kegiatan Kesenian Hadroh - Hamka Ghozali; Ziaulhaq; Fitriani (Journal of Cultural Relativism (JCR), 2025)
This study aims to examine the spiritual involvement of youth through the Hadroh art as a medium for religious development and character strengthening. In the era of globalization and digitalization, youth face various moral and spiritual challenges that may weaken their Islamic identity. Using a descriptive qualitative approach, this research explores how active participation in Hadroh fosters religious awareness, strengthens moral values, and enhances social solidarity. The findings reveal that Hadroh serves as an effective means of da’wah and Islamic character formation, where young participants experience spiritual engagement through chanting shalawat and practicing communal values. This activity not only reinforces religious and social bonds but also helps adolescents manage emotions, cultivate responsibility, and develop continuous religious motivation.